Hacking Gender Stereotypes: Girls’ Participation in Coding Clubs. - Carlana, Michela; Fort, Margherita (AEA Papers & Proceedings, 2022)
The article offers information about hacking gender stereotypes, along with mentions the girls' participation in coding clubs. It mentions that employment opportunities and wage growth have been rising more rapidly among occupations that require high levels of both math and social skills in the U.S.